Rancang Bangun Aplikasi Penjualan Dan Pengiriman Spare Part Komputer Pada Bismar Komputer Surabaya - Gigih Haris Pradana; Bambang Hariadi; Rahayu Arya Shintawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The sales department, warehouse, shipment are departments which should integrate to each other that sometimes give difficulties in communicating to each departments. So that, it is needed to make an appropriate application which can provide easier way for each department to communicate especially in selling and shipping process of computer spare part. Methods used in making the application of sales and delivery of spare parts is SDLC (System Development Life Cycle) waterfall model. This aplication integrates sales department, warehouse and shipment and also generate reports about the sale and delivery of spare parts at Computer Bismar Surabaya.